Energy, Risk and Governance The Case of Nuclear Energy in India - Wong, Catherine Mei Ling (Springer International Publishing, 2018)
This book is about how energy, risk and governance are intertwined in the development of the nuclear industry in India and its relationship with the Indian public. It provides a rare insider-view of how the nuclear establishment thinks about risk, contrasted with public understandings of nuclear risk. Energy, Risk and Governance presents a nuanced picture of why nuclear energy is still considered by some as a rational choice. This is in spite of its risks, the ambiguities in both expert and public risk perceptions, and the internal reflexivities that have emerged within the nuclear establishment as a result of the Fukushima-Daiichi disaster that is absent from public discourse. The insights in this book are not unique to India and similar observations can likely be made across the global nuclear industry. Reflecting on what this means for risk governance in practice, this book proposes practical suggestions and some tools that practitioners in the nuclear industry can use in public engagement, risk communication and deliberation at various stages of decision-making.